2003
DOI: 10.1146/annurev.biophys.32.110601.142520
|View full text |Cite
|
Sign up to set email alerts
|

The Crystallographic Model of Rhodopsin and Its Use in Studies of Other G Protein–Coupled Receptors

Abstract: G protein-coupled receptors (GPCRs) are integral membrane proteins that respond to environmental signals and initiate signal transduction pathways activating cellular processes. Rhodopsin is a GPCR found in rod cells in retina where it functions as a photopigment. Its molecular structure is known from cryo-electron microscopic and X-ray crystallographic studies, and this has reshaped many structure/function questions important in vision science. In addition, this first GPCR structure has provided a structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 131 publications
2
101
0
4
Order By: Relevance
“…Molecular model of the residues proposed to be part of the structural basis for the high constitutive activity in the ghrelin receptor. A, molecular model of the ghrelin receptor built over the inactive structure of rhodopsin (60,61). The seven helical bundle is displayed without the loops as viewed from the extra-cellular side.…”
Section: Figmentioning
confidence: 99%
“…Molecular model of the residues proposed to be part of the structural basis for the high constitutive activity in the ghrelin receptor. A, molecular model of the ghrelin receptor built over the inactive structure of rhodopsin (60,61). The seven helical bundle is displayed without the loops as viewed from the extra-cellular side.…”
Section: Figmentioning
confidence: 99%
“…3,[128][129][130] This is especially important due to the large number of important pharmacological targets within the large GPCR family. [131][132][133][134][135][136][137][138][139][140][141][142] In our simulation results, the nature of the coupling between a local conformational change and a large-scale helix and loop change may be similar across the GPCR family. This would imply that the effect of ligand binding to a GPCR is tightly regulated by a coupled set of energetic interactions, in a similar manner to that found within the retinal-rhodopsin system.…”
Section: Implications For Other Gpcr Systemsmentioning
confidence: 99%
“…This structure also allowed construction and validation of numerous prediction models of other GPCRs (reviewed in ref. [38]). Recent biochemical studies demonstrated the existence of detergent-resistant membrane microdomains in ROS and therefore a non-uniform distribution of lipids and proteins [39][40][41].…”
Section: Introductionmentioning
confidence: 99%